Major histocompatibility complex-restricted CD8+ cytotoxic T lymphocytes from horses with equine infectious anemia virus recognize Env and Gag/PR proteins. - McGuire, T C (1994)
Cytotoxic T lymphocytes (CTL) can control some viral infections and may be important in the control of lentiviruses, including human immunodeficiency virus type 1. Since there is limited evidence for an in vivo role of CTL in control of lentiviruses, dissection of immune mechanisms in animal lentiviral infections may provide needed information. Horses infected with equine infectious anemia virus (EIAV) a lentivirus, have acute plasma viremia which is terminated in immunocompetent horses. Viremic episodes may recur, but most horses ultimately control infection and become asymptomatic carriers. To begin dissection of the immune mechanisms involved in EIAV control, peripheral blood mononuclear cells (PBMC) from infected horses were evaluated for CTL to EIAV-infected cells. By using noninfected and EIAV-infected autologous equine kidney (EK) cells in 51Cr-release assays, EIAV-specific cytotoxic activity was detected in unstimulated PBMC from three infected horses. The EIAV-specific cytotoxic activity was major histocompatibility complex (MHC) restricted, as determined by assaying EIAV-infected heterologous EK targets, and was mediated by CD8+ T lymphocytes, as determined by depleting these cells by a panning procedure with an anti-CD8 monoclonal antibody. MHC-restricted CD8+ CTL in unstimulated PBMC from infected horses caused significant specific lysis of autologous EK cells infected with recombinant vaccinia viruses expressing EIAV genes, either env or gag plus 5' pol. The EIAV-specific MHC-restricted CD8+ CTL were detected in two EIAV-infected horses within a few days after plasma viremia occurred and were present after viremia was terminated. The detection of these immune effector cells in EIAV-infected horses permits further studies to determine their in vivo role.